Assessment of the Financial Health of Rural Hospitals After Implementation of the Georgia Rural Hospital Tax Credit Program - Apenteng, Bettye A. (JAMA Netw Open, 2021)
IMPORTANCE: In 2016, Georgia implemented the Rural Hospital Tax Credit Program, which allows taxpayers to receive a tax credit for contributions to qualifying rural hospitals in the state. Empirical evidence of the program’s association with the viability of the state’s rural hospitals is needed. OBJECTIVE: To examine the association of the tax credit program with the financial health of participating rural hospitals. DESIGN, SETTING, AND PARTICIPANTS: This longitudinal cross-sectional study used hospital financial data from the Centers for Medicare & Medicaid Services for 2015 to 2019. A difference-in-differences analytic approach was used to examine the association of the tax credit program with rural hospital financial health. Study participants included Georgia rural hospitals eligible to participate in the program. Comparison hospitals were selected from the southern states of Alabama, Florida, Mississippi, North Carolina, South Carolina, and Tennessee. EXPOSURES: Hospital participation in the Georgia Rural Hospital Tax Credit Program. MAIN OUTCOMES AND MEASURES: The primary outcome of the study was financial health measured with total margin, days cash on hand, debt-asset ratio, and average age of plant as well as a Financial Strength Index (FSI), which combined the previous measures to assess overall financial strength. RESULTS: The analytical sample included a balanced panel of 136 hospitals, with 47 Georgia Rural Hospital Tax Credit Program participants (18 [38%] critical access hospitals; 5 [11%] system affiliated; mean [SD] bed count, 60 [47]; mean [SD] Medicare inpatient mix, 52% [16]) and 89 comparison hospitals (43 [48%] critical access hospitals; 24 [27%] system affiliated; mean [SD] bed count, 52 [41]; mean [SD] Medicare inpatient mix, 67% [18]). Two years after implementation, program participation was associated with a 23% increased probability of good or excellent financial health (b = 0.23; 95% CI, 0.10-0.37; P < .001) and a 6.7-point increase in total margin (b = 6.67; 95% CI, 3.61-9.73; P < .001). CONCLUSIONS AND RELEVANCE: These early findings suggest that the Georgia Rural Hospital Tax Credit Program is associated with improvements in hospital financial health; however, additional studies are needed to assess the program’s long-term impact on the financial sustainability of Georgia’s rural hospitals.